Perceived Value’s Impact on Parent-Teacher Relationship among Preschool Parents: Mediating Roles of Service Quality and Social Media Use - Hua-Chen Lo; Tzu-Hua Wang; Ru-Si Chen (SAGE Open)
This study examines how parents’ perceived value influences the parent-teacher relationship in Taiwanese preschools, with service quality and social media use serving as mediating factors. A questionnaire-based survey was conducted, and data were analyzed using partial least squares structural equation modeling (PLS-SEM) to test both the measurement and structural models. The results confirm the proposed hypotheses and show that perceived value significantly shapes the parent-teacher relationship. In addition, service quality and social media use were found to fully mediate the relationship between perceived value and parent-teacher interaction. This study presents a comprehensive model of the factors influencing parent-teacher relationship in Taiwanese preschools. By highlighting the role of service quality and social media as mediators, the findings highlight the importance of improving communication and service delivery to enhance parent-teacher collaboration and ultimately foster stronger preschool partnerships. This study explores parents’ consideration of how perceived value affects the parent-teacher relationship in Taiwanese preschools, including service quality and social media use as mediating factors. Using a robust analytical framework, particularly partial least squares, we rigorously tested the measurement and structural models in the questionnaire. Our results confirm the hypotheses and reveal complex dynamics in Taiwanese preschool education. Our findings highlight the role of perceived value in shaping parents’ views of the parent-teacher relationship. Supported by a multiple mediation model, service quality and social media use act as mediators, indicating that perceived value significantly influences the parent-teacher relationship through full mediation. The study provides a comprehensive model for understanding and improving parent-teacher interactions, highlighting the benefits of improving communication, service delivery, and overall satisfaction. Insights from this research aim to improve preschool partnerships, foster a more collaborative environment, and increase educational services for the benefit of both parents and preschool educators.